Nilai-nilai Pendidikan Karakter dalam Komunikasi WhatsApp antara Mahasiswa dan Dosen - Nurul Hikma; Mayong Mayong; Hasriani Hasriani (SOCIETIES: Journal of Social Sciences and Humanities, 2023)
Abstract: The Values of Character Education in WhatsApp Communication between Students and Lecturers. Indonesian Language and Literature Education Study Program, Indonesian Language and Literature Department, Faculty of Language and Literature. This study aims to: (1) describe the form of character education values in WhatsApp communication between students and lecturers; and (2) describe the values of character education in WhatsApp communication between students and lecturers. This type of research is qualitative research. The research design used is descriptive qualitative. The data in this study are texts or sentences used in WhatsApp communication between students and lecturers. Sources of research data are students of the faculty of language and literature as informants. Data collection techniques used in this study were documentation, reading, and notes. The results of the study reveal that the values of character education in WhatsApp communication between students and lecturers include religiosity, nationalism, integrity, independence, and mutual cooperation. The data that were not found were with the sub-values of loving the environment, integrity with the sub-values of loyalty and anti-corruption and the value of inclusive character with the sub-values of anti-discrimination and non-violence. The functions found are educational functions, religious functions, social functions, cultural functions, and social functions. Keywords: Character education values, student and lecturer communication, WhatsApp.